Vitality continuation or over-commercialization? Spatial structure characteristics of commercial services and population agglomeration in historic and cultural areas. Issue 8 (December 2019) - Wang, Fang; Liu, Zhao; Shang, Shanshan; Qin, Yuelei; Wu, Bihu
In recent years, with rapid urbanization and development of tourism, historic and cultural areas have become characterized by strong vitality. However, a dilemma has arisen concerning their over-commercialization. In this study, 17 Chinese historic and cultural areas, and their surroundings within a radius of 1.5 km, were selected for research. Then, the spatial structure and population agglomeration associated with points of interest (POIs), including commercial service POIs and tourist attraction POIs, were analyzed, resulting in five principal findings. (1) In China, commercial services in historic and cultural areas have become an integral part of tourist attractions. (2) The relationships between the spatial structures of commercial service POIs and tourist attraction POIs can be classified into five types: fully encircled clustering, semi-surrounding clustering, overlapping clustering, contiguous clustering, and separate clustering. (3) Based on a POI kernel density analysis, historic and cultural areas can generally be classified into three categories: commercial service oriented areas, tourist attraction oriented areas, and commerce–tourism complexes. (4) The results illustrated that population agglomeration and spatial patterns of the POIs were tightly coupled; and this correlation was very consistent. The authors found that while living, shopping, and catering services were attractive in isolation, tourist attractions, accommodation, and leisure services often combined to form a shared space to attract business. The research results also provided insights into maintaining the balance between community life and commercial development of historic and cultural areas.